A Brief Overview of Claire White's An Introduction to the Cognitive Science of Religion. (20th April 2022) - Geertz, Armin W.
Abstract : This article provides a brief overview of Claire White's An Introduction to the Cognitive Science of Religion for the benefit of readers who have not had access to the book but are interested in following the critical discussion raised in this issue